Transcendental singularities for a meromorphic function with logarithmic derivative of finite lower order - Langley, J.K. (Springer Verlag, 2019)
It is shown that two key results on transcendental singularities for meromorphic functions of finite lower order have refinements which hold under the weaker hypothesis that the logarithmic derivative has finite lower order.